2015
DOI: 10.4236/ojapps.2015.512071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Size, Suspension Recycling and Substrate Pre-Treatment on the CVD Growth of Diamond Coatings

Abstract: CVD growth of uniform conformal polycrystalline diamond (PCD) coatings over complex three dimensional structures is very important material processing technique. It has been found that the nucleation and subsequent growth period is very critical for successful development of CVD diamond based technologies. There are many methods of enhancing diamond nucleation on foreign substrates-ultrasonic treatment with diamond seed suspension being the best among them. A combination of ultrasonic seeding (US) technique wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Nucleation density determines the faster grain coalescence phenomenon during chemical vapour deposition. It has been observed that DND seeds are much superior in enhancing nucleation of diamond than conventional micron size grits for seeding diamond nuclei on the foreign substrates [119]. The particle size of seeds is thus important in determining nucleation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleation density determines the faster grain coalescence phenomenon during chemical vapour deposition. It has been observed that DND seeds are much superior in enhancing nucleation of diamond than conventional micron size grits for seeding diamond nuclei on the foreign substrates [119]. The particle size of seeds is thus important in determining nucleation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The diamond seeding step before the growth can also affect the quality of the diamond film, grain size, thermal conductivity, and TBRs. , A high seeding density on the substrate, using diamond nanoseeds with densities above 10 11 cm –2 , can initiate a fast growth and diamond film coalescence, which could minimize the GaN decomposition under hydrogen plasma environment and thus improve the adhesion . A recent study has experimented with mixed-sized diamond seeding using microseeds and nanoseeds to grow CVD diamond films on GaN and AlN .…”
Section: Introductionmentioning
confidence: 99%